Management of Chronic Sinusitis - Fatmawati, Fatmawati; Suparmi, Suparmi (International Medical Journal Corp. Ltd, 2024)
Background: The literature on chronic sinusitis management highlights the complexity and multifactorial nature of chronic rhinosinusitis (CRS), necessitating a nuanced approach that combines medical and surgical interventions tailored to individual patient needs. Literature Review: (D Wright & Frenkiel, 2005) emphasize the significance of refined diagnostic criteria and personalized medical therapies in surgical management, particularly through the use of endoscopic sinus surgery (ESS) when maximal medical therapy fails. They highlight advancements in surgical techniques and instrumentation that have improved outcomes ((D Wright & Frenkiel, 2005)). Building on this foundation, the work of (B Cain & Lal, 2013) underscores the heterogeneity of CRS and the necessity for comprehensive medical management strategies that minimize the adverse effects of long-term corticosteroid and antibiotic use, advocating for novel topical therapies ((B Cain & Lal, 2013)). Conclusion: In conclusion, the literature collectively underscores the necessity for individualized treatment plans that incorporate both medical and surgical interventions, informed by the latest research and patient experiences. The integration of new therapeutic modalities, along with an emphasis on patient-centered care, reflects a progressive understanding of CRS management that aims to enhance patient outcomes and quality of life.